2018
DOI: 10.1136/jmedgenet-2018-105301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic classification in Prader-Willi syndrome: a multisite cohort study

Abstract: We report on molecular classes in PWS using advanced genomic technology in the largest cohort to date. LOH patterns in UPD15 may impact the risk of having a second genetic condition if the mother carries a recessive mutant allele in the isodisomic region on chromosome 15. The risk of UPD15 may also increase with maternal age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 20 publications
7
137
0
Order By: Relevance
“…It was anticipated that the larger areas of LOH (involving more genes), the higher the risk of carrying a second genetic disorder or atypical features in UPD patients. 4 Because of limited case numbers in our study, we were unable to identify the phenotypic differences between different subtypes of UPD. However, it is rational for clinicians to cautiously observe the atypical features from PWS patients with larger LOH.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It was anticipated that the larger areas of LOH (involving more genes), the higher the risk of carrying a second genetic disorder or atypical features in UPD patients. 4 Because of limited case numbers in our study, we were unable to identify the phenotypic differences between different subtypes of UPD. However, it is rational for clinicians to cautiously observe the atypical features from PWS patients with larger LOH.…”
Section: Discussionmentioning
confidence: 90%
“…Total isodisomy resulted from nondisjunction events in meiosis II and total heterodisomy from meiosis I nondisjunction error, whereas various numbers of crossing-over events could lead to segmental isodisomy. 7 Among 60 cases of PWS with segmental isodisomy, Butler et al 4 identified 25 cases with two segments and three cases with three segments of LOH, suggesting more than one crossing-over event in those cases. The most common LOH sites were proximal 15q12 and distal 15q26.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the markers we studied are from the pericentromeric regions of the respective chromosomes of origin, where cross‐overs are not expected to occur, this finding indicates either a previous maternal meiosis II (mat‐MII) nondisjunction or a postzygotic event. Indeed, in a number of cases of trisomy rescue (Butler et al., ; Chantot‐Bastaraud et al., ) a mat‐MII error has been documented. Similarly, the mechanism leading to the formation of the supernumerary i(12p), associated with Pallister‐Killian syndrome, has been proven to be prezygotic and of maternal origin, presumably occurring at MII as demonstrated by the presence of three genotypes at the distal 12p region and only two at the pericentromeric one (Blyth et al., ; Conlin et al., ).…”
Section: Reconstruction and Formation Mechanisms Of Ssmcmentioning
confidence: 99%
“…PWS is the most common syndromic cause of life‐threatening obesity with an estimated incidence of 1/10 000 to 1/25 000 live births, occurring equally in both males and females, and across all ethnicities . The errors in genomic imprinting that are causative for PWS (determined by a DNA methylation analysis) are classified as paternal deletion , which represents the majority of all cases of PWS (60%); maternal uniparental disomy ( UPD ) 15 , found in about 36%; and imprinting centre defect ( ID ), in 4% …”
Section: Introductionmentioning
confidence: 99%